Curriculum and the Life Erratic The Geographic Cure - Nissen, Leslie B.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Curriculum and the Life Erratic: The Geographic Cure lays bare the untold damage done to children who are forced to endure the toxic combination of "fermented parenting" (as author Leslie Nissen has termed it) and frequent family moves at the hands of alcoholic parents who perpetually seek the elusive Geographic Cure. While such parents deceive themselves that in the next new place, sobriety will prevail, their children know better. Alcoholics who chronically uproot their families for a fresh start usually carry along every reason to drink. For the school-age children of such cure-seeking alcoholics, the torment of life with a volatile, unpredictable and chronically intoxicated parent is intensified by the anguish of being (3z(Bthe new kid(3y (Bwho changes schools at the whim of the parent. Highly mobile children, bearing an alarmingly long list of prior schools, may be part of a group which Nissen calls Geographic Cure Children, whose chances of finding help are nearly non-existent, despite their acute need for care. The dilemma of this unique subset of Children of Alcoholics is examined via autobiographical, psychoanalytic and fictional lenses. Nissen also recounts her own urge to hit the road when diagnosed with cancer, and explores the Geographic Cure writ large, observing how the current (3z(Btesting frenzy(3y (Band clamor for cures for low test scores dominate educational policy. Could teachers$1 (Bpanic about accountability cause them to resent new students who appear at their classroom doors mid-year? Is education encumbered because, at the hands of policy-makers, educators are working the Life Erratic?s
Keywords: Education; Education; Education (general).